Finding the uncommon deal : a top New York lawyer explains how to buy a home for the lowest possible price - Bailey, Adam Leitman (Wiley, 2011)
Offers the secrets to negotiating the lowest prices for real estate, describing how to go beyond Internet listings to obtain on-the-ground intelligence about properties and leverage negotiating skills for success and savings.